Estructura de la negociación salarial e incentivos a innovar - Barcena-Ruiz, Juan Carlos; Campos, María Luz (Estudios de Economía, 2016)
In this article we analyse the effect that the sequence of salary negotiations hason the firm´s decisions about the adoption of new labour saving technologies.We show that if the cost of the innovation is sufficiently high, innovations arerelated with sequential as well with simultaneous negotiations. In addition, thecost of the innovation depends on the market size, increases in labour productivityresulting of the new technology and the reserve salary of workers.